Principles of politeness used and violated by Acehnese-speaking Khatibs in their Friday prayer sermons - Ramli Ramli; Ridwan Ibrahim; Kismullah Abdul Muthalib; Teuku Alamsyah; Ahmad Nubli Gadeng (Universitas Syiah Kuala, 2023)
This research focused on the politeness of the preachers (henceforth, Khatibs) in delivering sermons. The objective was to find out how politeness principles were applied in the Acehnese language sermons delivered by the Khatibs in Friday prayer processions in Aceh Besar, Indonesia. The data for this research was 15 Friday sermons given at seven sub-districts in Aceh Besar. This study used naturally occurring data from the Friday sermons collected over two months by recording them at 15 mosques within the area of Aceh Besar. Data were transcribed and analyzed using Grice’s maxim theory. The results showed that out of the six politeness maxims, only two maxims, the sympathy maxim, and the tact maxim were found and identified to be applied in the Friday prayer sermons. The sympathy maxim was dominantly used by the Khatibs with 52 occurrences or 68.4% of data, while the tact maxim was found to be used in 24 occurrences or 31.6% of data. Meanwhile, the approbation maxim, the agreement maxim, the modesty maxim, and the generosity maxim were not found in the data. This might be attributed to the nature of the discourse of the sermons as one-way dialogues. It can be concluded that Friday prayers only used the sympathy maxim and tact maxim of politeness because of the one-way communication of Friday sermons. The reasons for the absence of the other four politeness maxims are contextually discussed in this paper.